Numerical investigations of Aerodynamic characteristics prediction of high-lift low reynolds number airfoil - Boughou, Smail; Omar, Ashraf Ali; Elsyed, Omer A.; Aldheeb, Mohammed (Semarak Ilmu Publishing, 2022)
The Micro Aerial Vehicles (MAVs) operate at a critical range of low Reynolds number (Re). The implementation of the low (Re) aerodynamics for MAVs has brought interest into the study of high-lift low Re airfoils. Such investigations may bring new insight into the aerodynamic performance of MAVs flights. The aim of the current investigation is to exam different numerical methods in the aerodynamics prediction of high-lift low Reynolds number S1223 airfoil. For that purpose, the Spallart Allmaras (S-A), two equations SST K-ω and the four equations transition γ-Reθ SST turbulence models were used. Results revealed that the SA turbulence model can predict the pre-stall low angles of attack and provides a good agreement with experimental data and XFOIL results. Whereas the two-equation model SST-enhanced K-ɷ and the transition SST models predict better the unsteadiness of the stall behaviour. XFoil accurately predicts the highest lift coefficient, even if it occurs at a lower angle of attack. These results showed the promising ability of the transition SST selection in predicting the stall behaviour.